Key transcriptional regulators of neutrophil function in inflammation - Ai, Z (2021)
Neutrophils are important effector cells in innate immunity, possessing a wide range of effector functions, including reactive oxygen species (ROS) production, phagocytosis and chemotaxis. These properties enable neutrophils to rapidly respond to stimulation and orchestrate protective immunity. Currently, the transcriptional regulatory networks underlying neutrophil activation and function remain largely unexplored. Of note, there is partial understanding of transcription factors (TFs) that act as key regulators to control neutrophil development and inflammatory responses. Neutrophils undergo tightly controlled genomic and transcriptional changes while transitioning between bone marrow, blood, and tissue sites. However, the molecular mechanisms underlining neutrophil function during inflammation have yet to be fully elucidated. To determine the transcription factor networks that shape these responses, we have undertaken integrated transcriptional and chromatin analyses of neutrophils during acute inflammation and revealed distinct sets of putative transcription factors (TFs) associated with control of neutrophil differentiation and inflammatory responses.